KARAKTERISTIK ORGANOLEPTIK BISKUIT DENGAN FORTIFIKASI ABON IKAN SALMON (Oncorhynchus nerka) - Ramli Ramli (Faculty of Science and Technology University Ibrahimy, 2014)
This study uses a randomized complete block design (RAK) with one treatment factor is proportion of shredded salmon and wheat flour. There are seven levels of the proportion of shredded salmon and wheat flour, which is 5%: 95%, 10%: 90%, 15%: 85%, 20%: 80%, 25%: 75%, 30%: 70% and 35% : 65%. Seventh proportion of shredded salmon and wheat flour were repeated 3 times so that there are 21 experimental unit. Analysis biscuits were first done of organoleptic analysis include color, aroma, flavor and texture to get the best treatment with the number of trained panelists as many as five people. The best treatment is obtained and then carried to the 20 respeonden preference test to determine consumer acceptance and chemical analysis covering the water content, protein content, fat content, ash content, and carbohydrate content. From this research result that the biscuits with the proportion of fish meal 5% and wheat 95% produce the best biscuits on the results of organoleptic test with an average value of preference for color 5:30 (love), the average value of preference for the scent of 5.50 (like), a mean value of preference for sense of 5.60 (like), and the average value of preference for the texture 5:30 (love). Chemical test results biscuits best treatment had 3.87% moisture content, protein content 12:54%, ash content of 1.67%, 15:32% fat, and carbohydrate content of 66.38%.